2014
DOI: 10.1002/hipo.22344
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of 2‐arachidonoylglycerol hydrolysis produces antidepressant‐like effects and enhances adult hippocampal neurogenesis and synaptic plasticity

Abstract: The endocannabinoid ligand 2-arachidonoylglycerol (2-AG) is inactivated primarily by monoacylglycerol lipase (MAGL). We have shown recently that chronic treatments with MAGL inhibitor JZL184 produce antidepressant- and anxiolytic-like effects in a chronic unpredictable stress (CUS) model of depression in mice. However, the underlying mechanisms remain poorly understood. Adult hippocampal neurogenesis has been implicated in animal models of anxiety and depression and behavioral effects of antidepressants. We te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 78 publications
(133 reference statements)
3
59
0
1
Order By: Relevance
“…Accordingly, chronic stressinduced collapse of eCB signaling may be involved in the development of allostatic load from chronic stress and contribute to the development of psychiatric conditions, such as depression. This hypothesis is consistent with findings that augmenting eCB signaling in the presence of chronic stress can stabilize and curb stress-induced changes in plasticity and produce potential antidepressant-or anxiolytic-like effects (Bortolato et al, 2007;Hill et al, 2013b;Lomazzo et al, 2015;Sumislawski et al, 2011;Zhang et al, 2015;Zhong et al, 2014).…”
Section: Functional Role Of Ecb Signaling In the Neurobiological Effesupporting
confidence: 91%
See 1 more Smart Citation
“…Accordingly, chronic stressinduced collapse of eCB signaling may be involved in the development of allostatic load from chronic stress and contribute to the development of psychiatric conditions, such as depression. This hypothesis is consistent with findings that augmenting eCB signaling in the presence of chronic stress can stabilize and curb stress-induced changes in plasticity and produce potential antidepressant-or anxiolytic-like effects (Bortolato et al, 2007;Hill et al, 2013b;Lomazzo et al, 2015;Sumislawski et al, 2011;Zhang et al, 2015;Zhong et al, 2014).…”
Section: Functional Role Of Ecb Signaling In the Neurobiological Effesupporting
confidence: 91%
“…Consistent with this, central genetic 2-AG deficiency results in increased anxiety that can be reversed by acute normalization of 2-AG levels (Shonesy et al, 2014). There is also evidence that potentiation of 2-AG signaling can dampen anxiety induced by chronic stress (Sumislawski et al, 2011;Zhang et al, 2015; but see Lomazzo et al, 2015 for negative findings). These studies clearly support the notion that 2-AG also has a key role in regulating anxiety and stress responsivity.…”
Section: Functional Role Of Ecb Signaling In the Neurobiological Effementioning
confidence: 87%
“…Pharmacological blockade of its hydrolyzing enzyme MAGL produces anxiolytic-like effects (479,782,941). Genetic modification by adeno-associated virus-mediated overexpression of MAGL in hippocampal glutamatergic neurons of the mouse resulted in a 50% decrease in 2-AG tissue levels without affecting the content of AEA, and led to increased anxiety-like behavior (312).…”
Section: Mood and Emotionsmentioning
confidence: 99%
“…FAAH inhibitors increasing AEA brain levels enhance the activity of serotonergic neurons in the dorsal raphe nucleus and noradrenergic neurons in the nucleus locus ceruleus, thus eliciting antidepressant effects (295). Accordingly, 1) higher levels of FAAH in the rat frontal cortex and hippocampus may cause depressive-like disorders (885), and 2) chronic mild unpredictable stress, a model for depression, leads to impairment of 2-AG-mediated LTD in the CA1 region of the hippocampus, an effect prevented MAGL inhibition (942), which also enhances neurogenesis and LTP in the dentate gyrus (941). Accordingly, long-term antidepressant treatments increase 2-AG levels in different brain areas (803).…”
Section: Mood and Emotionsmentioning
confidence: 99%
“…159,160 Furthermore, the administration of 151 was demonstrated to produce gastroprotective and antidepressant-like effects post a 4 mg/kg intraperitoneal injection. 160,161 The determination of the binding mechanism indicated that 151 covalently and irreversibly bound to MAGL through the formation of the carbamylated-enzyme adduct ( Figure 56). intraperitoneal injection without resulting in cannabimimetic side effects including hypomotility, hypothermia and catalepsy.…”
Section: Carbamatesmentioning
confidence: 99%